A Home Energy Management Algorithm with Smart Plug for Maximized Customer Comfort - Elma, Onur; Selamogullari, Ugur Savas (IEEE, 2015)
Energy management systems are used for more efficient use of electric energy. Energy management systems generally just contain demand-side management. A possible solution for demand side management in the existing structures is the use of smart plugs. The smart plug can be defined as a port that monitors and records the parameters such as power consumed, the current drawn and connection point voltages of plugged devices and allows remote turning on/off of the plugged device when required. In this study, a new smart plug design is investigated that can provide power reduction without turning the plugged device off. The advantages of the developed smart plug based energy management system are stated in terms of consumer comfort and energy consumption.
Keywords: Smart plug; Home energy management; Demand response; Customer comfort; SYSTEM; Energy & Fuels; Engineering